When to screen for developmental language disorder: a review of age-specific evidence - Park, Ji Hyun; Chang, Min Cheol (Frontiers in Pediatrics, 2025)
Developmental language disorder (DLD) is a heterogeneous condition with challenges in determining the optimal timing for screening. Despite the complexities of early language development, clinical decisions must still be made regarding when to identify children at risk. Recent literature has emphasized the need for the age-specific evaluation of screening precision. This review aims to identify the earliest age for acceptable predictive validity. A narrative synthesis of studies evaluating the validity of DLD screening tools or protocols was conducted, covering ages below 2–4 years. Screening before age 2 demonstrates insufficient sensitivity as a standalone screening point. By age 2.5, several tools achieve sensitivity and specificity above 70%–80%, meeting recommended thresholds. At age 3, screening shows adequate concurrent validity. Screening at age 4 is more aligned with diagnosis than early detection. Based on existing evidence, 2.5 years is the earliest age at which DLD screening tools begin to demonstrate acceptable predictive performance. The findings may inform clinical guidelines on DLD screening and highlight the need for further age-stratified studies to refine DLD screening strategies.